Entrepreneurial Energy in a Far-From-Equilibrium Opportunity Driving Entrepreneurial Actions - Leong, David (Journal of Entrepreneurship, Business and Economics; Vol 9 No 1 (2021), 2021)
Disequilibrium and complexity are the distinguishing characteristics of entrepreneurial phenomena. How do the entrepreneurs arbitrage, leverage and benefit in the disequilibria and what spur them to action? The force that drives entrepreneurial ventures, from creation to sustaining through to exit, and then through innovation to extend the game or recreate another play is an imminent force that holds and sustains entrepreneurial momentum. Entrepreneurial energy, a coined terminology in this paper, is that endogenous force. There are scarce relevant researches. In particular, there is no specific mention of the “entrepreneurial energy” in the theory of entrepreneurship. The closest proxy is entrepreneurial passions. Passion cannot be held in equal doses throughout the venture pathway. John Maynard Keynes coined the phrase "animal spirits" in his 1936 book “The General Theory of Employment, Interest and Money”. He used the term to describe emotions that influence human economic behaviour. Animal spirits create an ambience of trust and faith and are necessary for human actions, more than quantitative logic. Keynes felt animal spirits were needed as a goad to economic action rather than inaction. Schumpeter came up with the German word Unternehmergeist, meaning entrepreneur-spirit, adding that these individuals controlled the economy because they are responsible for delivering innovation and technological change. Whether its entrepreneurial energy, animal spirit or entrepreneur-spirit, it is a force that needs reckoning with in entrepreneurship study. Entrepreneurship is a science of turbulence and change, not continuity. A certain force causes turbulence. Such is the force in entrepreneurship like the wind is felt but not seen through the leaves' ruffle but not the wind itself. This paper will demonstrate that entrepreneurial energy can be better understood if examined through the lens of complexity and quantum science to address this omission. The indeterminacy in uncertainties and chaos theories best describe the dynamically complex, fast, volatile, uncertain disrupted, diverse, ambiguous, hyper-turbulent and hyperconnected entrepreneurial ecosystem. This paper contributes to entrepreneurship research by developing a complexity-based and uncertainty-based definition of entrepreneurial energy. This energy will be referred to in the context of the entrepreneurial ecosystem (space) where the entrepreneurs (object) exist over time. Building on this definition, it connects the research on the entrepreneur to venture-level complexity and entrepreneurial multi-finalities/pathways. It explores how these force originates and is sustained- that will influence entrepreneurial emergence and continuation- from the intentionality of entrepreneurs and the coherence of entrepreneurial activities, through the exploration and exploitation of perceived opportunities within the entrepreneurial ecosystem. Beyond theory development, it explores how scholars can examine entrepreneurial energy as a complex play of forces through interpretivist methods. This paper has implications for entrepreneurs and policymakers. Research paper Keywords: Entrepreneurship; Complexity science; Far-from-equilibrium; Structuration theory Reference to this paper should be made as follows: Leong, D. (2021). Entrepreneurial Energy in a Far-From-Equilibrium Opportunity Driving Entrepreneurial Actions. Journal of Entrepreneurship, Business and Economics , 9 (1), 1–31.